2020
DOI: 10.1111/rego.12354
|View full text |Cite
|
Sign up to set email alerts
|

Private regulation, public policy, and the perils of adverse ontological selection

Abstract: What problems can private regulatory governance solve, and what role should public policy play? Despite access to the same empirical evidence, the current scholarship on private governance offers widely divergent answers to these questions. Through a critical review, this paper details five ontologically distinct academic logicscalculated strategic behavior; learning and experimentalist processes; political institutionalism; global value chain and convention theory; and neo-Gramscian accountsthat offer diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 172 publications
0
25
0
Order By: Relevance
“…McDermott et al 2010;Lenox & Nash 2003). This is problematic since recent research making these distinctions on standards (Judge-Lord et al 2020) and impacts (Grabs et al 2021) has revealed fundamental differences about whether compliance would be expected to lead to increased, or reduced, environmental degradation and economic opportunities. Unpacking these differences is important if students of public-private interactions are to generate meaningful conclusions about their problemsolving potential.…”
Section: Differences Surrounding Problem Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…McDermott et al 2010;Lenox & Nash 2003). This is problematic since recent research making these distinctions on standards (Judge-Lord et al 2020) and impacts (Grabs et al 2021) has revealed fundamental differences about whether compliance would be expected to lead to increased, or reduced, environmental degradation and economic opportunities. Unpacking these differences is important if students of public-private interactions are to generate meaningful conclusions about their problemsolving potential.…”
Section: Differences Surrounding Problem Definitionsmentioning
confidence: 99%
“…Each illustrates different types of interaction, proposes novel hypotheses for why particular interactions occur and, either explicitly or implicitly, highlights the utility of the "governance sphere" concept. Grabs et al (2021) began on a metatheoretical note by observing that the study of public and private governance interactions is replete with ontological assumptions. These assumptions are derived from six particular theoretical traditions that have been actively used to study private governance since its inception.…”
Section: Differences Surrounding Problem Definitionsmentioning
confidence: 99%
“…14 The observation that private governance schemes and their stakeholders lobby in support of private rules and private rulemaking is noteworthy since this topic has received scant attention in the literature so far. Using Fuchs' (2007) application of the three-dimensional political power perspective (instrumental, structural, and discursive power) on private governance, we can see that scholars have predominantly addressed the structural (or rulemaking) and discursive (or legitimizing) power of private governance, including when discussing interactions between public and private governance (Cutler et al 1999;Hall & Biersteker 2002;Bernstein & Cashore 2007;Paterson 2010;Lister 2011;Wright & Nyberg 2014;Green & Auld 2017;Grabs et al 2021). The instrumental power of private governance-and lobbying and interest representation by private governance schemes specifically-has not received systematic analytical attention, even though it is highlighted in issue-specific case studies (for organic agriculture, for example, see Gibbon 2008).…”
Section: Discussionmentioning
confidence: 99%
“…1999; Hall & Biersteker 2002; Bernstein & Cashore 2007; Paterson 2010; Lister 2011; Wright & Nyberg 2014; Green & Auld 2017; Grabs et al . 2021). The instrumental power of private governance—and lobbying and interest representation by private governance schemes specifically—has not received systematic analytical attention, even though it is highlighted in issue‐specific case studies (for organic agriculture, for example, see Gibbon 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation